UPAYA MENINGKATKAN MINAT BACA DIKALANGAN REMAJA DESA WIROBITING MELALUI LAYANAN BIMBINGAN KELOMPOK - Emilia Prasida Sari Emilia Prasida (STKIP PGRI SUMENEP, 2022)
The purpose of this study was to determine interest in reading among adolescents in the village of Wirobiting by increasing interest in reading through group guidance services. The method used in this research is using qualitative research methods with data collection methods in the form of interviews and observations. The study was conducted on adolescents aged around 14-17 years. data obtained from interviews. for data analysis using descriptive method. Based on the results of the study, it can be concluded that several factors causing the low reading interest of teenagers in Wirobiting Village are environmental factors, family factors, peer factors, and facilities factors. the use of group guidance services in the study was able to increase reading interest among village youth.